PHENYLPROPANOIDS, EUGENOL SCAFFOLD, AND ITS DERIVATIVES AS ANTICANCER - Fadilah, Fadilah; Yanuar, Arry; Arsianti, Ade; Andrajati, Retnosari (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Eugenol (EU) is a phenylpropene, an allyl chain-substituted guaiacol. EU is a member of the phenylpropanoids class of chemical compounds. It is a colorless to pale yellow oily liquid extracted from certain essential oils especially from clove oil. Further, chemopreventive agents might be used singly or in combination with chemotherapy or radiotherapy for the more effective treatment of cancer by enhancing the efficacy of these modalities with minimal side effects and toxicity. Considering that EU scaffold may be a prospective chemopreventive agent, its potent antitumor ability to interfere with solid cancer cell growth and its molecular mechanism were evaluated as an initiative toward the development of a novel strategy for cancer treatment. This review article will conduct that EU as the antiproliferative activity and molecular mechanism of the EU induced apoptosis against the cancer cells and animal models. Keywords: Eugenol, Derivatives of eugenol, Scaffold, Anticancer, Phenylpropanoids.